DEVELOPMENT OF E-COMMERCE IN UKRAINE UNDER CONDITIONS OF DIGITAL TRANSFORMATION, MOBILE TECHNOLOGIES, AND ECONOMIC INSTABILITY CAUSED BY MILITARY ACTIONS - Бурка, Богдан О.; Шкода, Мар’яна С. (Journal of Strategic Economic Research, 2025)
The article substantiates that e-commerce in Ukraine is gradually becoming one of the key mechanisms for adapting the national economy to contemporary challenges. During the full-scale war, it functions not only as an alternative sales channel but also as a critically important infrastructure for maintaining entrepreneurial activity, employment, and consumer demand. The digitalization of trade is accelerating under external pressure – on the one hand, due to the growth of mobile traffic and the shift of consumer behavior to online environments, and on the other, due to the limited physical availability of traditional retail formats. Under these conditions, e-commerce is no longer just a technological option, but a necessity that requires rapid adaptation of business models, logistics solutions, and modes of customer interaction. Particular attention must be paid to issues such as digital inequality, regional disparities in access to online services, unstable infrastructure, energy supply disruptions, and a decline in consumer purchasing power – all of which directly affect the operation of e-commerce. Modern Ukrainian e-commerce is evolving under conditions that demand constant restructuring. Businesses are implementing mobile platforms, localizing logistics routes, strengthening their presence on social media, and working on communication personalization. The resilience of the sector largely depends on the level of digital competencies of entrepreneurs, their ability to self-learn, and openness to new managerial approaches. At the same time, public initiatives in particular, the Diia.Business platform – play an important role in creating a basic infrastructure that enables small and medium-sized enterprises to continue operating under conditions of instability. The relevance of this topic stems not only from the need to overcome the consequences of war but also from the formation of a digital foundation for the future economy. Understanding the barriers that hinder the development of e-commerce, the specific strategies businesses use for adaptation, and the role digital skills play in this process enables more precise formulation of post-war transformation strategies. This study focuses on a systemic analysis of constraints, behavioral models, and managerial practices under multilayered crisis conditions. Ultimately, the level of digital flexibility will determine not only the capacity of Ukrainian businesses to recover but also the long-term competitiveness of the national economy. The decisions made today will shape the institutional memory and practices that will underpin the business models of the digital age.